2009
DOI: 10.1152/ajpregu.90992.2008
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone decreases blood pressure and renal injury in a female mouse model of systemic lupus erythematosus

Abstract: -Women with systemic lupus erythematosus (SLE) exhibit a high prevalence of hypertension and renal injury. Rosiglitazone (Rosi), a peroxisome proliferator activator receptor gamma (PPAR␥) agonist, has renal protective and antihypertensive effects. We tested whether Rosi ameliorates hypertension and renal injury in a female mouse model of SLE (NZBWF1). Thirty-week-old SLE and control (NZW/LacJ) mice (n Ն 6/group) were fed Rosi (5 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 in standard chow) or standard chow for 4 wk. SLE mice had incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
87
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 57 publications
12
87
0
Order By: Relevance
“…The pivotal role for the kidney in the long-term control of blood pressure is well known and a decreased renal blood flow can mechanistically contribute to the hypertensive shift in the pressure natriuresis relationship. Importantly, prevalent hypertension contributes to the greater cardiovascular risk in patients with SLE (25,33,35,51), and we previously demonstrated that, similar to humans with SLE, NZBWF1 mice develop hypertension (40,41,53,54). Under the current experimental conditions, the hypertension that is observed in conscious animals is largely muted as a result of the anesthesia.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The pivotal role for the kidney in the long-term control of blood pressure is well known and a decreased renal blood flow can mechanistically contribute to the hypertensive shift in the pressure natriuresis relationship. Importantly, prevalent hypertension contributes to the greater cardiovascular risk in patients with SLE (25,33,35,51), and we previously demonstrated that, similar to humans with SLE, NZBWF1 mice develop hypertension (40,41,53,54). Under the current experimental conditions, the hypertension that is observed in conscious animals is largely muted as a result of the anesthesia.…”
Section: Discussionmentioning
confidence: 86%
“…Renal cortical protein expression of AT1R, ANG II receptor type-2 (AT2R) and renin were determined using standard Western blot analysis methods, as previously described (53,54). Rabbit polyclonal anti-AT1R antibody (1:500; Alomone Laboratories, Jerusalem, Israel), rabbit polyclonal anti-AT2R antibody (1:500; Alomone Laboratories), goat polyclonal anti-renin (1:250; Santa Cruz Biotechnology, Santa Cruz, CA) and mouse anti-␤-actin (1:5,000; Abcam, Cambridge, MA) were used.…”
Section: Animalsmentioning
confidence: 99%
“…More recently, it was demonstrated that rosiglitazone treatment decreased blood pressure and was effective in preventing the progression of renal injury in deoxycorticosterone acetate-salt hypertension through reducing the overexpression of ET-1 in the kidney 21 and that rosiglitazone decreased blood pressure and renal injury in a female mouse model of systemic lupus erythematosus accompanied by a reduction of urinary ET. 22 The mechanisms underlying the vasoprotective effects of TZDs remain largely unknown. The present study clearly shows that 24-hour treatment with rosiglitazone suppressed ET-1-induced and ET A R-mediated contraction only in rings with endothelium.…”
Section: Tian Et Al Ppar-␥ Reduces Vasoconstriction Via Et B Rdiscussionmentioning
confidence: 99%
“…22,25 The prevalence of atherosclerosis and hypertension in diabetic patients is approximately twice compared with that of nondiabetics. 26 Conversely, the chance of developing type 2 diabetes mellitus in atherosclerosis and hypertensive individuals is also 2-to 4-fold higher than that in normotensive individuals.…”
Section: Tian Et Al Ppar-␥ Reduces Vasoconstriction Via Et B Rdiscussionmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor γ (PPARγ) agonists are widely prescribed for the pharmacological treatment of type 2 diabetes by their insulin-sensitizing properties. PPARγ agonists also exert anti-inflammatory and immunomodulatory effects, and the beneficial impacts of rosiglitazone were reported for the amelioration of the autoantibody production, renal disease, and atherosclerosis in MRL-lpr mice depending on the induction of adiponectin [1] and also in NZBWF1 mice [2]. SLE is associated with increased circulating apoptotic autoantigens and increased type I interferon (IFN) signaling which simulate the production of autoantibody including anti-dsDNA antibodies [3].…”
Section: Systemic Lupus Erythematosus (Sle) Is An Inflammatory Autoimmentioning
confidence: 99%